Special aspects organization of tutor support for secondary school students - Osadcha, K. P. (Problems of Engineer-Pedagogical Education, 2018)
The paper presents the age characteristics of teenagers according to it the special aspects of tutor support for secondary school students acquiring specific features. The paper discusses these specific characteristics on the basis with the analysis of scientific papers (Kovaleva T.M., Kunash M.A., Isakova, O.A., Tregubova, O.G. and others).Tutor support at the secondary school is understood as pedagogical activities, the essence of which is development of preventive student competencies, proficiency and skills of independent educational and life course planning, formation and implementation of individual educational programs, proficiency and problem-solving skills. It is reported that tutor activities with teenagers are mainly aimed at keeping up their interest in learning orientation in the selection of items of interest and preprofile training. It was found that the main tutor activities with secondary school students are diagnostic methods, a project method, a portfolio method, and such forms as consultations, trainings, competitions, educational and research activities.